Application of Multi-stage Filtration for COD Reduction in Biodiesel Wastewater from Methyl Ester Production - Anandya Zulham Valensyah (JOBC, 2025)
This study investigates a multi-layer filtration column consisting of sand, zeolite, and activated carbon for reducing Chemical Oxygen Demand (COD) in methyl ester fractionation wastewater. Pilot-scale experiments were conducted at a flow rate of 1.5 m³·h-¹, resulting in an Empty-Bed Contact Time (EBCT) of only 2.31 seconds. Under this short residence time, the system achieved limited single-pass COD reductions ranging from 0.308% to 0.424%, with an average of 0.356%. A first-order kinetic model predicted a theoretical removal of 0.1815%, which is within the same order of magnitude as the experimental results. This alignment confirms that contact time is the primary limiting factor in system performance. Minor differences between theoretical and measured values may result from variations in activated carbon, first-break flow, and analytical uncertainty. The results indicate that the current configuration is insufficient for achieving meaningful COD removal under the tested operating conditions. Substantial improvement would require increasing EBCT, adding more activated carbon, or redesigning the system into multiple stages. The findings provide quantitative guidance for scaling and optimizing filtration-based pretreatment for industrial wastewater applications.